Pengaruh Komunikasi, Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan Studi Pada Kantor Wilayah XII Direktorat Jenderal Kekayaan Negara (DJKN) Banjarmasin - Andi Susanto; Hastin Umi Anisah (Universitas Lambung Mangkurat, 2013)
This research aims to find out and analyze the influence among communication (X ), leadership (X ), and work motivation (X ) as indefendent variables either 1 2 3 partially or simultaneously toward employee’s performance (Y) as dependent variable at Kantor Wilayah XII DJKN Banjarmasin. The method of this research used questionnaire with 32 employees of Kantor Wilayah XII DJKN Banjarmasin as a sample and it has been selected from population as 45 emplyees. The variables measurement uses Likert’s Scale technique with weighting scale from 1 to 5. To find out the correlation among 1 X X 2 3 variables X towards Y uses statistical technique of correlation analysis, multiple linear regression and to test the significance rate uses F test and t test processed with SPSS Program. 1 The result of research concludes that there is a positive significant influence from each indefendent variable’s toward the dependent variable. From the three indefendent variables, the highest percentage (25.9%) is the communication (X ) as compared with the two other independent variables. And there is a significant simultaneously influence from the three independent variables toward the variable of employee’s performance.